Clinical Features of CMV-Associated Anterior Uveitis - Chan, Nicole Shu-Wen; Chee, Soon-Phaik; Caspers, Laure; Bodaghi, Bahram (Ocular immunology and inflammation, 2018)
Cytomegalovirus (CMV) anterior uveitis is the most common ocular manifestation of CMV disease in immunocompetent individuals. It is thought to be due to a local reactivation of latent CMV and is usually unilateral. The acute form presents as Posner-Schlossman Syndrome, a recurrent hypertensive anterior uveitis with few granulomatous keratic precipitates. There are geographic differences in the chronic form of CMV anterior uveitis. Asian patients commonly present as Fuchs Uveitis Syndrome with diffuse stellate keratic precipitates, while the European patients present with a chronic hypertensive anterior uveitis with fewer keratic precipitates that are brown in color and located inferiorly. Characteristic features of CMV anterior uveitis include mild anterior chamber inflammation, elevated intraocular pressure, stromal iris atrophy. Synechiae, macular edema and retinitis are typically absent. CMV disease may also be associated with the development of corneal endotheliitis with a reduced endothelial cell count. Long-term complications include glaucomatous optic neuropathy and cataract formation.